Experimental Evaluation of Torque Performance of Voltage and Current Models using Measured Torque for Induction Motor Drives - Ibrahim M. Alsofyani; Tole Sutikno; Yahya A. Alamri; Nik Rumzi Nik Idris; Norjulia Mohamad Nordin; Aree Wangsupphaphol (Institute of Advanced Engineering and Science, 2015)
In this paper, two kinds of observers are proposed to investigate torque estimation. The first one is based on a voltage model represented with a low-pass filter (LPF); which is normally used as a replacement for a pure integrator to avoid integration drift problem due to dc offset or measurement error. The second estimator used is an extended Kalman filter (EKF) as a current model, which puts into account all noise problems. Both estimation algorithms are investigated during the steady and transient states, tested under light load, and then compared with the measured mechanical torque. In all conditions, the torque estimation error for EKF has remained within a narrow error band and yielded minimum torque ripples, which motivate the use of the EKF estimation algorithm in high performance control drives of IMs for achieving high dynamic performance.